Wielokryterialne spojrzenie na produkcję zbóż w UE - Kukuła, Karol; Strojny, Jacek (A Multicriterial Look at Cereal Production in EU, 2006)
The paper presents results of an analysis of the cereal production patterns in EU. The study takes production volume, production per capita and yields into consideration. The outcome of the research is the countries ranking and objects' typology against production patterns. The leading countries positioning is mostly determined by production and yield indexes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 508-513